An Analysis of Samra Habib’s We Have Always Been Here (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2022)
Samra Habib is a queer Pakistani Canadian writer, photographer, and activist recognized by Lambda Literary in 2019 for her memoir We Have Always Been Here. In the memoir, Habib discusses her experiences as a queer person of color, religious minority, and immigrant. I contextualized her lived experiences within the various health frameworks I was introduced to in Professor Kirsty Clark’s “LGBTQ Health Disparities” course—life course perspective, minority stress theory, intersectionality, and the social-ecological model—to examine how Habib’s intersecting identities shaped the challenges she faced and her transformation into a leading LGBTQ+ activist and role model.For additional context, listen to the author's reflection on the piece below.